Influence of best thawing method to reduce microbial load in red meats - Obaidi, Dahfir A .A. (The Iraqi Journal of Veterinary Medicine, 2016)
The current study was carried out at the college of veterinary medicine, University of Baghdad, for three months. The main objective of this study was to evaluate the effect of different thawing method of frozen minced red meat to reduce its bacterial load. Four thawing methods were used where the tap water at 18 °C for two hours was used in the first method, while the hot water at 40 °C for 1.5 hours was used in the second method and in the third method the frozen minced meat samples were left at room temperature (28 °C) for two hours, where as in the fourth method the frozen meat samples were stored inside the refrigerator at 4 °C for 20 hours. Data revealed that there were significant differences (P<0.05) in the mean values of total aerobic bacterial counts between the tap water, room temperature and the refrigeration thawing methods and were lower than the standard limits recorded by ICOSQ and were ranged between 4.84 to 6.0 log cfu/gm of meat. On the other hand these data revealed that thawing in hot water had non significantly (P>0.05) the highest counts of total aerobic bacterial counts in comparison to the other mentioned three thawing methods and were ranged from (6.04–7.9) log cfu/gm of meat, which were higher than the standard limits recorded by ICOSQC. In conclusion on the basis of this investigation, it is pointed out that thawing of frozen minced red meat inside the refrigerator for overnight was the best and suitable to get meat with stable microbiological quality.